Chemically induced mouse models of acute and chronic intestinal inflammation - Wirtz, Stefan; Popp, Vanessa; Kindermann, Markus; Gerlach, Katharina; Weigmann, Benno; Fichtner-Feigl, Stefan; Neurath, Markus (Nature Protocols, 2017)
Inflammatory bowel diseases (IBDs) result in diarrhea and abdominal pain with further potential complications such as tissue fibrosis and stenosis. Animal models help in understanding the immunopathogenesis of IBDs and in the design of novel therapeutic concepts. Here we present an updated version of a protocol we published in 2007 for key models of acute and chronic forms of colitis induced by 2,4,6-trinitro-benzene sulfonic acid (TNBS), oxazolone and dextran sulfate sodium (DSS). This protocol update describes an adaptation of the existing protocol that modifies the technique. This protocol has been used to generate improved mouse models that better reflect the nature of IBDs in humans. In TNBS and oxazolone colitis models, topical administration of hapten reagents results in T-cell-mediated immunity against haptenized proteins and luminal antigens. By contrast, to generate DSS colitis models, mice orally receive DSS, causing death of epithelial cells, compromising barrier function and causing subsequent inflammation. The analysis of the acute colitis models can be performed within 1-2 weeks, whereas that of the chronic models may take 2-4 months. The strengths of the acute models are that they are based on the analysis of short-lasting barrier alterations, innate immune effects and flares. The advantages of the chronic models are that they may offer better insight into adaptive immunity and complications such as neoplasia and tissue fibrosis. The protocol requires basic skills in laboratory animal research.
EVALuna2:33810